2014
DOI: 10.1371/journal.pone.0098558
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Mitochondrial Genome of Meloidogyne graminicola (Tylenchina): A Unique Gene Arrangement and Its Phylogenetic Implications

Abstract: Meloidogyne graminicola is one of the most economically important plant parasitic-nematodes (PPNs). In the present study, we determined the complete mitochondrial (mt) DNA genome sequence of this plant pathogen. Compared with other PPNs genera, this genome (19,589 bp) is only slightly smaller than that of Pratylenchus vulnus (21,656 bp). The nucleotide composition of the whole mtDNA sequence of M. graminicola is significantly biased toward A and T, with T being the most favored nucleotide and C being the least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 59 publications
(104 reference statements)
8
48
0
Order By: Relevance
“…It has been suggested that mitochondrial phylogenetic markers including variable number tandem repeats could help resolve the population diversity better than nuclear markers (Lunt et al, 1998;Besnard et al, 2014;Sun et al, 2014;Humphreys-Pereira and Elling, 2015). Testing additional phylogenetic markers would resolve if our populations belong to M. graminicola or to other cryptic species.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that mitochondrial phylogenetic markers including variable number tandem repeats could help resolve the population diversity better than nuclear markers (Lunt et al, 1998;Besnard et al, 2014;Sun et al, 2014;Humphreys-Pereira and Elling, 2015). Testing additional phylogenetic markers would resolve if our populations belong to M. graminicola or to other cryptic species.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer RNA (trn) genes were identified using tRNAscan-SE 1.21 (Schattner et al, 2005) with the settings described by Humphreys-Pereira and , and by using the MITOS pipeline (Bernt et al, 2013). The secondary structures of trn genes from M. graminicola predicted by Besnard et al (2014) and Sun et al (2014) were re-analyzed in this study using tRNAscan-SE 1.21 and MITOS, and manually annotated by searching for anticodons. The ribosomal RNA genes rrnL and rrnS were identified through comparisons with other Meloidogyne spp.…”
Section: Mtdna Genome Annotationmentioning
confidence: 99%
“…Tandem Repeats Finder software was used to identify tandem repetitive elements (Benson, 1999). The gene architecture of the three mt genomes described in this study was compared with the mt genomes of M. chitwoodi, M. incognita and M. graminicola reported previously (Sun et al, 2014;Besnard et al, 2014).…”
Section: Mtdna Genome Annotationmentioning
confidence: 99%
See 2 more Smart Citations